Characteristics and Performance Test of the MQ-135 Sensor in the Organophosphate Pesticide Residue Detection System in Fruits and Vegetables - Asmaul Ma'rufah; Muhamad Azwar Annas (BULETIN FISIKA, 2026)
Organophosphates are compounds that we often find in vegetables and fruits. Organophosphates have several health impacts if consumed excessively and over a long period of time. This study aims to test the characteristics and performance of the MQ-135 sensor in the organophosphate pesticide residue detection system in fruits and vegetables. The MQ-135 sensor was chosen because of its sensitivity to various gaseous compounds, including volatile compounds resulting from pesticide degradation. The research method includes testing the sensor response to variations in the concentration of organophosphate pesticide solutions with 3 frequently used brands, namely kanon, diazinon and curacron. First, the MQ-135 was calibrated in clean air for 24 hours to obtain a baseline. After obtaining the baseline, the sensor was tested with concentration variations of 0-100 ppm in multiples of 10. Based on the research results, overall, the MQ-135 sensor showed good detection capabilities for the three pesticides, with the highest sensitivity in pesticide A, namely 325.645, where pesticide B has a value of 21.836 and pesticide C is 24.436. The best linearity value was obtained for pesticide B, which was 0.9969, while pesticides A and c were 0.9443 and 0.9933, respectively. However, at low concentrations, the sensor still showed instability, especially for pesticide A. This character indicates that the MQ-135 is suitable for use as a rapid screening tool (rapid test) to detect the presence of organophosphate pesticide residues, but requires additional calibration and further validation for quantitative precision measurements.